ASSOCIATION OF THYROID HORMONE LEVELS WITH LUTEAL PHASE DEFICIENCY IN INFERTILE WOMEN - Nasir , Sabeen; Ziaullah, Sara; Alam, Sadaf; Khan, Muhammad Mumtaz; Ahmad, Sajjad; Khan, Hina (Journal of Postgraduate Medical Institute, 2022)
Objectives: To find out the association of thyroid hormone levels with Luteal Phase Deficiency (LPD) Methodology: This prospective study was conducted at Peshawar Medical College, from April to August 2013. The sample size was 125 infertile women of the reproductive age group (18-42 years) selected through consecutive sampling technique. On the 22nd and 23rd of the menstrual cycle, endometrial biopsies were performed. Chemiluminescence Immunoassay was used to estimate the serum levels of the thyroid hormones. SPSS version 19 was used to conduct the statistical analysis. The Chi-square test was used to see whether there was any statistically significant difference between the endometrial findings of patients with normal thyroid profiles and those who had elevated thyroid hormone levels. It was deemed statistically significant when the probability value was p<0.05. Results: The majority of infertile patients (n=99) had normal thyroid profiles, followed by hyperthyroid cases (n=23). Only three turned out to be hypothyroid. There was no significant difference in endometrium between the patients with normal and increased thyroid hormone levels. Conclusion: Although no statistically significant association between the thyroid hormones levels and the endometrium in cases of Luteal Phase Deficiency could be found in this study, their role cannot be ignored and needs further evaluation